A diet containing high- versus low-daidzein does not affect bone density and osteogenic gene expression in the obese Zucker rat model. Issue 10 (3rd October 2019) - Rochester, Eric; Wickman, Brooke E.; Bell, Andrea; Simecka, Christy; Clayton, Zachary S.; Hakkak, Reza; Hooshmand, Shirin
Abstract : Phytoestrogens are nonsteroidal plant compounds with similar chemical structures to mammalian estrogen capable of mimicking the effect of estrogen in selective tissues. Abstract : Phytoestrogens are nonsteroidal plant compounds with similar chemical structures to mammalian estrogen capable of mimicking the effect of estrogen in selective tissues. A diet rich in phytoestrogens is associated with a variety of health benefits including decreased risks for heart disease, breast cancer, and osteoporosis. Obesity has long thought to be associated with improved bone density due to increased mechanical loading, but recent literature suggests obesity may actually decrease bone health. Daidzein, a soy-derived phytoestrogen, has been shown to improve parameters of bone health in lean animal models of osteoporosis but has not been tested in obese animals. Following a one-week acclimation to a standard AIN-93G diet, 19 five-week-old female obese Zucker rats (OZR) were randomly assigned to a modified AIN-93G diet containing either high daidzein (HD, 0.121 g kg −1 feed) or low daidzein (LD, 0.01 g kg −1 feed). After 8 weeks, tibias and femurs were removed to assess true density (Archimedes principal), mechanical strength (three-point bending test), and femoral osteogenic gene expression. Serum was collected to assess osteocalcin and deoxypyridinoline. Our results indicated that there were no significant differences between the measures for tibial or femoral true density or mechanical strength for the rats in the HD and LD diet groups. Similarly, there were no significant differences in gene expressions related to osteogenic pathways, or serum biomarkers of bone formation and resorption. Overall, an increased dose of daidzein from soy protein supplementation does not elicit an improvement in markers of bone health in obese Zucker rats.